Optimum Conditions for Glutaminase Production by Serratia marcescens N1 - Zbar, Nedhaal S; Al-Shaibani, Abdul Wahid B; Jasim, Hameed M (Al-Nahrain Journal of Science, 2018)
Optimum conditions for glutaminase production by Serratia marcescens N1 in glutamine broth medium were studied. Results showed that maximum glutaminase production was achieved when S.marcescens was cultured in production medium supplemented with starch as a sole source for carbon and energy at a concentration of 0.5%, meat extract as a nitrogen source at a concentration of 0.5%, pH8 and inoculated with a count of 2×104 CFU/ml of fresh bacterial culture, then incubated in a shaker incubator (150 rpm) at 30oC for 18 hrs. Under these conditions, specific activity of crude glutaminase produced in culture filtrate was 5.8U/mg protein.